Coronary Angiography Safety between Transradial and Transfemoral Access - Santosh Kumar Sinha; Vikas Mishra; Nasar Afdaali; Mukesh Jitendra Jha; Ashutosh Kumar; Mohammad Asif; Ramesh Thakur; Chandra Mohan Varma (Cardiology Research and Practice)
Background and Aim. The aim of study was to evaluate safety, feasibility, and procedural variables of transradial approach compared with transfemoral approach in a standard population of patients undergoing coronary catheterization as one of the major criticisms of the transradial approach is that it takes longer overall procedure and fluoroscopy time, thereby causing more radiation exposure. Method. Between January 2015 and December 2015, a total of 1,997 patients in LPS Institute of Cardiology, GSVM Medical College, Kanpur, UP, India, undergoing coronary catheterization were randomly assigned to the transradial or transfemoral approach. Result. Successful catheterization was achieved in 1045 of 1076 patients (97.1%) in the transradial group and in 918 of 921 patients (99.7%) in the transfemoral group (p=0.001). Comparing the transradial and transfemoral approaches, fluoroscopy time (2.46±1.22 versus 2.83±1.31 min; p=0.32), procedure time (8.89±2.72 versus 9.33±2.82 min; p=0.56), contrast volume (67.52±22.54 versus 71.63±25.41 mL; p=0.32), radiation dose as dose area product (24.2±4.21 versus 22.3±3.46 Gycm2; p=0.43), and postprocedural rise of serum creatinine (6±4.5% versus 8±2.6%; p=0.41) were not significantly different while vascular access site complications were significantly lower in transradial group than transfemoral group (3.9% versus 7.6%; p=0.04). Conclusion. The present study shows that transradial access for coronary angiography is safe among patients compared to transfemoral access with lower rate of local vascular complications.